2006
DOI: 10.2215/cjn.01431005
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Artery and Other Vascular Calcifications in Patients with Cystinosis after Kidney Transplantation

Abstract: Cystinosis, an autosomal recessive disorder of lysosomal cystine accumulation, results from mutations in the CTNS gene that encodes the lysosomal cystine transporter, cystinosin. Renal tubular Fanconi syndrome occurs in infancy, followed by rickets, growth retardation, photophobia, and renal failure, which requires renal transplantation at approximately 10 yr of age. Treatment with cysteamine decreases cellular cystine levels, retards renal deterioration, and allows for normal growth. Patients with a history o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 41 publications
2
21
0
2
Order By: Relevance
“…In contrast, oral cysteamine therapy represents an attractive targeted therapeutic modality. Long-term oral cysteamine administration in patients with cystinosis [4] has been shown effective in decelerating glomerular deterioration [16, 17], eliminating signs and symptoms of encephalopathy and the gross abnormalities on MRI [18], depleting cystine in parenchymal organs (liver and muscle) [19], and lowering the frequency of hypothyroidism [20], swallowing abnormalities [21], coronary artery and other vascular calcifications [22], and posterior eye segment defects [23]. As we view cystine accumulation in the bone marrow a likely contributor to this patient’s pancytopenia, oral cysteamine administration represents the promising available therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, oral cysteamine therapy represents an attractive targeted therapeutic modality. Long-term oral cysteamine administration in patients with cystinosis [4] has been shown effective in decelerating glomerular deterioration [16, 17], eliminating signs and symptoms of encephalopathy and the gross abnormalities on MRI [18], depleting cystine in parenchymal organs (liver and muscle) [19], and lowering the frequency of hypothyroidism [20], swallowing abnormalities [21], coronary artery and other vascular calcifications [22], and posterior eye segment defects [23]. As we view cystine accumulation in the bone marrow a likely contributor to this patient’s pancytopenia, oral cysteamine administration represents the promising available therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Blood pressure usually returns to normal after removal of the native kidney. Calcification of various vessels, primarily the coronary arteries, is one of the late complications of cystinosis in patients with transplants [106]. High-resolution CT scans have revealed calcifications in the internal carotid arteries, coronary arteries, aortic arch and abdominal aorta.…”
Section: Late Disease Complicationsmentioning
confidence: 99%
“…Most patients with vascular calcifications had not received significant cysteamine therapy, which is consistent with the conclusion that cystinosis itself, and not drug exposure, is a risk factor for this complication. Adult patients should be carefully monitored for myocardial ischemia; some may require stenting or bypass surgery [106]. The hypercholesterolemia of cystinosis [107] also puts patients at increased risk of developing cardiovascular complications.…”
Section: Late Disease Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ueda et al found increased coronary and vascular calcifications in cystinosis patients and hypothesized that the accumulation of intracellular cystine itself may be a risk factor for vascular calcifications. They advised to screen older patients with cystinosis for this complication (Ueda et al 2006). We hypothesize that cystine accumulation in blood vessels might increase atheroma formation or arterial stiffness and therefore increase the risk for cardiovascular disease CVD.…”
Section: Introductionmentioning
confidence: 99%